Impact of Project Based Learning on critical thinking skills and language skills in EFL context: a review of literature - Mohamed Razali, Abu Bakar; Joanna, Joseph Jeyaraj; Sulaiman, Tajularipin; Song, Xinke (Sciedu Press, 2024)
In the domain of Teaching English as a Foreign Language (TEFL), the cultivation of critical thinking skills (CTSs) and language skills (LSs) is imperative for the academic development of learners. Project Based Learning (PBL), characterized by its integration of real world challenges and emphasis on collaborative learning, demonstrates significant potential to positively influence the development of CTSs and LSs in English as a Foreign Language (EFL) learners. This systematic review of literature meticulously evaluates the effects of PBL on fostering critical thinking skills CTSs and language skills LSs among EFL learners over recent decades. It assimilates insights from a range of empirical studies, elucidating how PBL activities enhance EFL learners’ critical thinking skills more effectively compared to conventional teaching methodologies. Additionally, this review underscores the beneficial impacts of PBL on language skills, encompassing vocabulary acquisition, speaking, writing, and reading comprehension, which are attributed to its focus on authentic tasks and practical real world applications. The implementation of PBL is instrumental in promoting deeper engagement in learning within EFL classrooms. Moreover, the perceptions of PBL by EFL learners and teachers constitute a significant component of the findings. EFL learners typically demonstrate favorable attitudes towards PBL, while EFL teachers recognize its efficacy in nurturing critical thinking and creativity , acknowledging challenges in its practical execution and assessment design. Conclusively, the review pinpoints existing research gaps and delineates prospective research trajectories. There exists an exigent need for comprehensive exploration into the mechanisms by which PBL augments skill development, longitudinal investigations into its enduring impacts, and research across diverse educational settings. The incorporation of technology within PBL frameworks and the preparedness of teachers are identified as pivotal areas for further inquiry.